2014
DOI: 10.1111/ecog.01078
|View full text |Cite
|
Sign up to set email alerts
|

Food web structure changes with elevation but not rainforest stratum

Abstract: Changes in species richness along elevational gradients are well documented. However, little is known about how trophic interactions between species and, in particular, the food webs that these interactions comprise, change with elevation. Here we present results for the first comparison of quantitative food webs in forest understorey and canopy along an elevational gradient. Replicate quantitative food webs were constructed for assemblages involving 23 species of cavity‐nesting Hymenoptera and 12 species of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 59 publications
(78 reference statements)
4
48
2
1
Order By: Relevance
“…A decline of parasitism towards higher elevations is likely, as the frequency of trophic interactions decreases polewards [59] and local elevation gradients reflect large-scale climatic gradients. To our knowledge, only two recent studies from subtropical Australia have addressed this topic and found a decrease of parasitism with elevation [18,46], which we support. Higher parasitism at lower and warmer lower elevation might be caused by higher attack rates of parasitoids, as demonstrated in controlled warming experiments [60].…”
Section: (C) Influence Of Elevation On Host-parasitoid Interactionssupporting
confidence: 81%
See 1 more Smart Citation
“…A decline of parasitism towards higher elevations is likely, as the frequency of trophic interactions decreases polewards [59] and local elevation gradients reflect large-scale climatic gradients. To our knowledge, only two recent studies from subtropical Australia have addressed this topic and found a decrease of parasitism with elevation [18,46], which we support. Higher parasitism at lower and warmer lower elevation might be caused by higher attack rates of parasitoids, as demonstrated in controlled warming experiments [60].…”
Section: (C) Influence Of Elevation On Host-parasitoid Interactionssupporting
confidence: 81%
“…The properties of such interactions can mathematically be quantified by various indices describing the structure of species interaction networks [16,17]. Thus, relating network properties to the environment can provide insight on how trophic interactions are influenced by changing habitat conditions [9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no previous study focused on leaf‐chewing assemblages. Inconsistent results obtained by previous studies suggest that the vertical patterns of parasitism are guild‐, latitude‐, or site‐dependent (Chaij et al., 2016; Morris et al., 2015; Paniagua et al., 2009; Sobek, Tscharntke, Scherber, Schiele, & Steffan‐Dewenter, 2009). The parasitism rate decreased as the season progressed, in accordance with another study on leaf‐chewing Lepidoptera in a temperate forest (Le Corff, Marquis, & Whitfield, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, studying herbivore–parasitoid communities in forest canopies could enhance our understanding of their structure and diversity (Stireman, Cerretti, Whitmore, Hardersen, & Gianelle, 2012). Moreover, investigating differences in ecological communities along habitat gradients could help us to recognize the factors that determine community structure (Morris, Sinclair, & Burwell, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation